An economic evaluation of the randomized controlled trial of topical corticosteroid and home‐based narrowband ultraviolet B for active and limited vitiligo (the HI‐Light Vitiligo Trial). (4th November 2020) - Sach, T.H.; Thomas, K.S.; Batchelor, J.M.; Perways, A.; Chalmers, J.R.; Haines, R.H.; Meakin, G.D.; Duley, L.; Ravenscroft, J.C.; Rogers, A.; Santer, M.; Tan, W.; et al.
Summary: Background: Economic evidence for vitiligo treatments is absent. Objectives: To determine the cost‐effectiveness of (i) handheld narrowband ultraviolet B (NB‐UVB) and (ii) a combination of topical corticosteroid (TCS) and NB‐UVB compared with TCS alone for localized vitiligo. Methods: Cost‐effectiveness analysis alongside a pragmatic, three‐arm, placebo‐controlled randomized controlled trial with 9 months' treatment. In total 517 adults and children (aged ≥ 5 years) with active vitiligo affecting < 10% of skin were recruited from secondary care and the community and were randomized 1: 1: 1 to receive TCS, NB‐UVB or both. Cost per successful treatment (measured on the Vitiligo Noticeability Scale) was estimated. Secondary cost–utility analyses measured quality‐adjusted life‐years using the EuroQol 5 Dimensions 5 Levels for those aged ≥ 11 years and the Child Health Utility 9D for those aged 5 to < 18 years. The trial was registered with number ISRCTN17160087 on 8 January 2015. Results: The mean ± SD cost per participant was £775 ± 83·7 for NB‐UVB, £813 ± 111.4 for combination treatment and £600 ± 96·2 for TCS. In analyses adjusted for age and target patch location, the incremental difference in cost for combination treatment compared with TCS was £211 (95% confidence interval 188–235), corresponding to a risk difference of 10·9% (number needed to treat = 9). The incremental cost was £1932 per successful treatment. The incremental difference in cost for NB‐UVB compared with TCS was £173 (95% confidence interval 151–196), with a risk difference of 5·2% (number needed to treat = 19). The incremental cost was £3336 per successful treatment. Conclusions: Combination treatment, compared with TCS alone, has a lower incremental cost per additional successful treatment than NB‐UVB only. Combination treatment would be considered cost‐effective if decision makers are willing to pay £1932 per additional treatment success. Abstract : What is already known about this topic? Vitiligo is a common skin condition with significant psychological impact. Topical corticosteroids (TCS) are standard care for vitiligo. Narrowband ultraviolet B (NB‐UVB) is only available in secondary care as full‐body treatment. Economic evidence for handheld NB‐UVB in combination with TCS is absent. What does this study add? Combination treatment, compared with TCS alone, has the lowest incremental cost per successful treatment. Whether this is considered cost‐effective depends on decision makers' judgement on how much they are willing to pay to achieve a successful treatment. Generic utility instruments, such as the EuroQol 5 Dimensions 5 Levels, may not be appropriate for vitiligo studies due to high ceiling effects. Measurement of quality of life for this condition warrants further research. This study provides results that can be compared with those of new emerging vitiligo treatments.